2001
DOI: 10.1107/s1600536801016051
|View full text |Cite
|
Sign up to set email alerts
|

Mn1-xFexS,x\simeq 0.05, an example of an anti-wurtzite structure

Abstract: The mineral rambergite, hexagonal manganese sulfide, is found to crystallize in the inverse wurtzite structure, i.e. the wurtzite type structure but with the opposite absolute configuration, which can also be named anti‐wurtzite. Rambergite was first found in the Garpenberg area, Dalarna, Sweden. The sample used in this investigation contained approximately 5% iron, as determined by microprobe analysis, giving the overall composition Mn1‐x Fex S, x 0.05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…MnS minerals with β and γ structures have been much more recently reported upon: rambergite (γ-MnS) has been discovered in 1996 in Sweden [21] whereas browneite (β-MnS) was found in a meteorite collected in Poland in 2012 [22]. We limit our review to homogeneous or heterogeneous nanostructures that comprise pure MnS with at least one dimension smaller than 100 nm (some MnS sub-microcrystals are included when of particular interest).…”
Section: Introductionmentioning
confidence: 99%
“…MnS minerals with β and γ structures have been much more recently reported upon: rambergite (γ-MnS) has been discovered in 1996 in Sweden [21] whereas browneite (β-MnS) was found in a meteorite collected in Poland in 2012 [22]. We limit our review to homogeneous or heterogeneous nanostructures that comprise pure MnS with at least one dimension smaller than 100 nm (some MnS sub-microcrystals are included when of particular interest).…”
Section: Introductionmentioning
confidence: 99%
“…60°20' N, long. 16°13.5' E), where various exotic skarn mineral assemblages have been noted to exist (Eriksson and Kalinowski, 2001;Holtstam, 2002;Kolitsch and Holtstam, 2002;Nysten, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The sample containing the new mineral presented here was collected in situ at the 900 m level of the Garpenberg Norra mine (60°20′N, 16°13.5′E), where various exotic skarn mineral assemblages have been noted to exist (Eriksson and Kalinowski, 2001; Holtstam et al , 2001; Holtstam, 2002; Kolitsch and Holtstam, 2002; Nysten, 2003). Garpenbergite was first spotted by one of the authors (K.G.)…”
Section: Introductionmentioning
confidence: 99%
“…More recently, naturally occurring minerals with β- and γ-MnS structure have been described. Rambergite (γ-MnS) was discovered in 1996 in Sweden [ 3 ]. In 2012, extraterrestrial browneite (β-MnS) was found in a meteorite collected in Poland [ 4 ].…”
Section: Introductionmentioning
confidence: 99%